Κοινωνική Πολιτική, Κράτος Πρόνοιας και Μακροχρόνια Φροντίδα στην Ελλάδα σε σύγκριση με την Ευρώπη Οι προκλήσεις στην αυγή του 2020 - Ιωάννου, Αλέξανδρος; Αποστολάκης, Ιωάννης; Σαράφης, Παύλος (My University, 2020)
Introduction: The evolution of social policy has resulted in the development of different social states. The characteristics of the social states are determined by two main factors, namely the different levels of public and private involvement, first, in meeting social needs and, second, in providing social protection. Purpose: Description of the main features of long-term care as well as the recipients, the ways and structures of its provision and analysis of the indicators of the Long-Term Care (LTC) provided in Greece in comparison with the rest of the Europe. Material and Method: A bibliographic review of relevant articles was made in the Medline/Pubmed and Google Scholar Electronic Databases as well as in books, scientific journals and websites with the following keywords: social policy, welfare state, long-term care, indicators LTC. Results: In Greece, delays in the development of an integrated social policy framework resulted in the emergence of a mixed model. In particular, the aforementioned element coupled with Greece’s particular geopolitical and socio-economic characteristics, has led to Greece’s classification under the Southern model, along with the other southern European countries. The past decades, to address the rise in the aging population and the increased needs, the establishment of LCT has been a major priority for developed European countries. Conclusions: In Greece, the fragmented and inadequate establishment resulted in ranking lower in the indicators. Thus, immediate measures and initiatives are required and necessary to effectively address future challenges, that the country will confront.
Social policy, welfare state and long-term care in Greece compared to Europe. The challenges at the dawn of 2020
Keywords: Kοινωνική πολιτική; Κράτος πρόνοιας; Mακροχρόνια Φροντίδα Υγείας; Δείκτες ΜΦΥ